Determinants of feeding practices and growth of Filipino infants a longitudinal study - Nguyen, Trung Tin (Thesis(Master of Science in Epidemiology)-- University of the Philippines Manila.)
This study is a secondary analysis of a prospective cohort study composed of 2,265 normal birthweight infants followed up over a period of one year. Outcome variables are breastfeeding practices and anthropometric measurement (such as weight and height which are measured at birth or 7 days, and at 2, 4, 6, 8, 10 and 12 months).
The association between feeding patters within the first four months of life and socio-economic, demographic, health sector, and food industru factors were determined by using polytomous logistic regression. The multiple linear regression was used to summarize weight or height in terms of the areas under the growth curve and feeding patterns in the first four months, socio-economic and demographic, biological, food industry and health sector factors, and morbidity of infants. The factors positively associated with breastfeeding practice in early infancy are low socio-economic status, residential place in rural are, multiparous mother, home delivered children, and not received free sample of formula. The results of the study show that breastfeeding in the first four months has a beneficial effect from birth to one year of life, especially in low socio-economic families. Socio-economic status, sex of infants, diarrhea, first child of mother are main determinants of physical growth. Delivery place far from home, vaccination against Diphtheria-Pertussis-Tetanus, and receive free sample of formula food determine weight development. Residential place was effect on the height growth of infants.
The following recommendations are proposed based on the results of the study: a) promoting full breastfeeding for the first four months, in both urban and rural area, especially in low socio-economic class; b) promoting of breastfeeding in the health facility, particularly in maternity ward and for primiparous women; c) banning advertisement of formula promotion of free formula sample in health facilities; d) increasing gender awareness and better nutrition for female infants; e) increasing coverage of vaccination; f) promoting reasonable introduction of weaning food after four months; g) giving more attention to infants of multiparous women; h) preventing diarrhea among infants.
Keywords: Breasfeeding -- Philippines; Infants -- Philippines; Infants -- Growth